An Assessment Of The AFL Mask® And LUNA Wallmount, The New Developments In The AirPurifier Industry For Preventing The Airborne Pathogens - Ghosh, Nabarun; Vitale, Jay; Bell, Jessica; Ray Mtech, Ashmita; Goyal, Shaily; Howard, Aubrey; Banerjee, Prabir (European Scientific Journal, ESJ, 2020)
The current unprecedented situation with the COVID-19 (Coronavirus Disease 2019) poses a great challenge to the scientific world, demanding immediate development of technologies to fight with and prevent transmission of pathogens, especially in regards to airborne pathogens and surface contaminants. It also urges us to reevaluate designs of advanced Personal Protective Equipment (PPE). We have been working on the development and assessment of the AFL-Photo Catalytic Oxidation (AFLPCO®) Nanotechnology to combat with airborne pathogens and different forms of impurities and pollutants present in the indoor air. Various types of facemasks are available in the world market and have become the most important personal protective equipment for healthcare workers and the public. Depending upon their filters, they can provide protection against dreaded contagious diseases and several types of pollution. With the current 2 spread of the COVID-19 Pandemic, facemasks and powerful air purification equipment are considered as lifesaving apparatus necessary for survival and living a healthy life. The facemasks filter fine airborne particles from reaching the respiratory system and prevent infection. We have designed a new type of facemask, AFL Mask® and LUNA Wall Mount Sanifier® air purification unit to combat with the airborne pathogen and increased air pollution. The AFL Mask® has proven to prevent the entry of the PM2.5 and airborne pathogen up to 99% and provide internal air, reducing the chances of building up moisture on the face. This newly designed AFL Mask® and LUNA Wall Mount Sanifier® can be used to prevent the pathogens and particulate matters significantly. We also tested the LUNA Wall Mount Sanifier® (LNT2-6000 Model), AFL Car Sanifier® and AFL Mask® for Ozone emission. All the equipment tested were proven safe to international standards in terms of Ozone emission.